Friendship quality in adolescence and social adjustment in the peer group - Freitas, Miguel (2018)
Friendships in adolescence are fundamental for social, emotional and cognitive development. However, differences in the quality of the relationship with a best friend may also be associated with adolescents’ psychosocial adjustment. The goal of this study was to identify different profiles of friendship quality, contrasting them regarding positive and negative features of this relationship, as well as youth’s social adjustment in the peer group. 821 participants from 7th grade (M=13 years old) reported on their perception of best friendship quality and sociometric nominations assessed social adjustment in the peer group. Three profiles emerged from hierarchical clusters analysis based on positive features of friendship quality, namely high-, medium- and low-quality friendships. Such profiles were significantly different in global quality and in all positive qualitative features of friendship: High-quality friendships were significantly higher in companionship, validation, help, support, intimacy, and conflict resolution strategies, whilst low-quality friendships had significantly lower values in all such dimensions. Sex differences revealed that girls experienced more intimate disclosure and validation and caring within their friendship dyads. Regarding negative features, adolescents in high-quality friendships reported less frequent conflict. As for social adjustment, youth in high quality friendships were considered by peers as the least anxious-withdrawn, excluded and victimized, but the most prosocial and popular/sociable. Participants in low-quality friendships were characterized by opposite scores. Findings highlight the significance of friendship in this developmental period, particularly, regarding friendship quality in young adolescents’ social milieu.